2009
DOI: 10.1002/ejoc.200801181
|View full text |Cite
|
Sign up to set email alerts
|

Cycloaddition Reactions of 1‐Alkyl‐3,4,5‐triphenyl‐1,2‐diphosphacyclopenta‐2,4‐dienes

Abstract: 1‐Alkyl‐3,4,5‐triphenyl‐1,2‐diphosphacyclopenta‐2,4‐dienes 1, obtained by alkylation of sodium 1,2‐diphospha‐3,4,5‐triphenylcyclopentadienide, exhibit dual reactivity in cycloaddition reactions: as dienes (with maleic anhydride and maleimide) or as dienophiles (with 2,3‐dimethylbutadiene). Thermolysis of 1 occurs with a [1,5] sigmatropic shift to form a [2+2] cyclodimerization product.(© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2009)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…16 According to the calculations, the 31 P CSs essentially depend on the isomeric structure varying within 100 ppm (Table S11, ESI †). 103 Conclusions A comparative analysis of calculated (GIAO) versus experimental 31 P NMR CSs for a wide range of organophosphorus model compounds was carried out. 8b).…”
Section: Application Of 31 P Nmr Css To Isomeric Structure Determinationmentioning
confidence: 99%
“…16 According to the calculations, the 31 P CSs essentially depend on the isomeric structure varying within 100 ppm (Table S11, ESI †). 103 Conclusions A comparative analysis of calculated (GIAO) versus experimental 31 P NMR CSs for a wide range of organophosphorus model compounds was carried out. 8b).…”
Section: Application Of 31 P Nmr Css To Isomeric Structure Determinationmentioning
confidence: 99%
“…In contrast, 2R phosp holes, which are formed from 1R phospholes at high tem peratures via R [1,5] sigmatropic shift, contain the highly reactive P=C bond and easily react with both dienes and dienophiles. 8 Earlier, 9 we have demonstrated that 1 alkyl 3,4,5 triphenyl 1,2 diphosphacyclopenta 2,4 dienes (1 alkyl 1,2 diphospholes) combining the fragments of 1R and 2R phospholes are chemically similar to both tautomeric forms: they are thermally stable like 1R phos pholes and are highly reactive in cycloaddition reactions like 2R phospholes.…”
mentioning
confidence: 98%
“…The sum of bond angles at the two phosphorus atoms of 2a and 3a is different: for caged P1 ∼270 • , and for bridging P10 ∼300 • [20][21][22]. There are eight chiral centers in 2a and 3a (Scheme 1); P1 has R and P10 has S configuration [15].…”
Section: Resultsmentioning
confidence: 96%